APLIKASI ADMINISTRATIF SURAT MENYURAT MENGGUNAKAN METODOLOGI PEMODELAN BERBASIS OBJEK - Harry Purnomo; Nani Tachjar (Faculty of Computer Science Universitas Indonesia, 2014)
Correspondence systems is often called administrative experience makes the applicant a letter of frustated. Once the letter is made, there should be a signature of the competent authority to legalize the letter. If these officials can not be found immediately, then the signing of a letter will be delayed. System admininstrative correspondence in this article takes a case study in IKPIA Perbanas, especially the demand letter from a student who photographed start running until the proposed system. As per the procedure, the system requests this certificate will be accepted by the student within 3 days from the date of the request. But in fact, the time required may be longer than it should. So when students need it in urgent circumstances, this can not be accommodated by the system adopted IKPIA Perbanas. Solution to solve this problem with an application system where modeling applications using object-based methodology. The general methodology used to model a system that can also be applied to the administrative system of correspondence.